Generation Y employees: understanding their workplace desires / Rosliza Md Zani, Syukriah Ali and Anita Abu Hassan - Md Zani, Rosliza; Ali, Syukriah; Abu Hassan, Anita (Universiti Teknologi MARA, Kedah, 2023)
Generation Y, also known as millennials, constitutes a sizable portion of the modern labor force. As this generation continues to dominate the job market, it is essential for organizations to understand their workplace preferences and expectations. This generation comprised of individuals born between the early 1980s and the late 1990s, and they have been described as a group seeking purpose, autonomy, and work-life balance. Understanding the desires of Generation Y in the workplace necessitates a holistic approach that takes into account various aspects of their professional lives. From purpose and meaning to worklife balance, career growth opportunities to technology and collaboration, feedback and recognition to diversity and inclusion, Generation Y employees have expectations that are distinct from those of prior generations in which they offer distinctive perspectives and values that could shape their careers. It is essential to foster a positive and productive work environment to identify and resolve their specific workplace desires.